Síntese de bis-iminas e bis-aminas funcionalizadas e avaliação de suas atividades contra células de câncer, fungos e como antioxidantes - Lucas Micqueias Arantes (2014)
In this work, thirty eight compounds were synthesized from condensation between hydroxybenzaldehydes (ortho, meta, and para) with phenylenediamines (ortho, meta, and para), of aromatic dialdehydes (ortho, meta, and para) with aminophenols (ortho, meta, and para) and benzoic aminoacids (ortho, meta, and para). All the compounds were obtained with yields 53% to 99%. Some of these reactions afforded cyclic compounds, such as benzoimidazole (two compounds) and imineisoindoline (five compounds). Seventeen acyclic bis-imines were reduced to bis-amines using sodium borohydride and cerium chloride. Two palladium complexes were prepared with bis-imines and one bis-amine was converted in to the respective platinum complex. Fifteen new compounds were synthesized in this work. Seventeen synthesized compounds were assayed in vitro against nine humans tumor cell lines: NCI-ADR/RES (ovarian cancer resistant to multiple drugs); NCI-H460 (Lung); PC-3 (prostate); OVCAR-3 (ovary); U251 (gliome, SNC); UACC-62 (melanoma); MCF-7 (breast); HT-29 (colon); K562 (leukemia). The cell line UACC-62 (melanoma) was the most susceptible for the evaluated compounds. Several compounds showed a broad spectrum of action in concentrations from 1 to 10 g/mL. One acyclic bis-imine presented a total inhibition of growth (TIG) four times higher than the positive control (doxorubicin), against the cell line NCI-ADR/RES (resistant ovary). All the compounds, except for the metallic complexes, were evaluated against the following pathogenic fungi of clinical interest: Candida albicans ATCC 18804, Candida krusei ATCC 20298, Candida parapsilosis ATCC 20019, Candida tropicalis ATCC 00750, Candida glabrata ATCC 32608, Cryptococcus neoformans ATCC 32608, Cryptococcus gattii ATCC 28957, and Candida dubliniensis CBS 7987. Several compounds have displayed some kind of activit Cryptococcus neoformans being the most susceptible to the four assayed compounds, showing inhibition levels near thoses achieved with the positive control (fluconazole). The free radical scavenging activity was evaluated for thirty five compounds using DPPH and superoxide anion radical methods. In both procedures the most of the compounds showed better anti-oxidant activities than that achieved with the positive control (resveratrol). In general, the bis-amines were more efficient than bis-imines.